STUDI DESKRIPTIF IMPLEMENTASI KEARIFAN LOKAL SEBAGAI UPAYA PENGUATAN IDENTITAS DAN KARAKTER PESERTA DIDIK KELAS IV DI MADRASAH IBTIDAIYAH - Larasati, Mentari Tiara; ‘Aini, Aulia Nur; Ati, Syaharani Kusumaning; Fatimah, Vivi Nurin; Nurjanah, Mely; Adi, Nugroho Prasetya (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2025)
ABSTRACT This study aims to analyze the implementation of local wisdom in learning at MI Ma’arif Gondang as a strategy to strengthen students’ identity and character, in line with the Independent Curriculum which emphasizes contextual learning based on cultural values. Employing a descriptive qualitative approach, data were collected through in-depth interviews with the principal, fourth-grade teacher, and vice principal for curriculum, supported by direct classroom observations and documentation of teaching and learning activities. The findings indicate that local wisdom has been integrated mainly into thematic subjects, local language instruction, and the Pancasila Student Profile Strengthening Project (P5), covering approximately 30% of the overall learning process. Examples of implementation include processing data related to Wonosobo’s traditional foods, exploring regional vocabulary, and tracing the origins of hamlet names. These activities have been shown to enhance student participation, foster a sense of belonging, and deepen understanding of local cultural identity. Nevertheless, several challenges persist, such as the limited documentation of local culture in the Gondang area, the absence of systematically developed lesson plans incorporating cultural elements, and a scarcity of relevant reference materials. These findings highlight the need for comprehensive institutional support, active collaboration among educators, targeted teacher training, and the development of culturally responsive teaching resources to ensure that the integration of local wisdom becomes more effective, relevant, and sustainable in meeting the needs of students in the era of globalization. ABSTRAK Penelitian ini bertujuan untuk menganalisis implementasi kearifan lokal dalam pembelajaran di MI Ma’arif Gondang sebagai strategi penguatan identitas dan karakter peserta didik, sejalan dengan Kurikulum Merdeka yang menekankan pembelajaran kontekstual berbasis nilai budaya. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik pengumpulan data melalui wawancara mendalam bersama kepala sekolah, guru kelas IV, dan wakil kepala sekolah bidang kurikulum, disertai observasi langsung dan dokumentasi proses belajar mengajar. Hasil penelitian menunjukkan bahwa integrasi kearifan lokal telah dilakukan terutama pada mata pelajaran tematik, Bahasa Daerah, dan Proyek Penguatan Profil Pelajar Pancasila (P5) dengan capaian sekitar 30% dari keseluruhan pembelajaran. Contoh implementasi mencakup pengolahan data terkait makanan khas Wonosobo, eksplorasi kosakata daerah, serta penelusuran asal-usul nama dusun. Aktivitas-aktivitas ini terbukti mampu meningkatkan partisipasi siswa, menumbuhkan rasa memiliki, serta memperdalam pemahaman terhadap identitas budaya lokal. Meski demikian, penerapan kearifan lokal masih menghadapi sejumlah kendala, antara lain minimnya dokumentasi budaya di wilayah Gondang, ketiadaan Rencana Pelaksanaan Pembelajaran (RPP) yang secara sistematis memuat unsur budaya lokal, serta keterbatasan sumber referensi. Temuan ini menegaskan pentingnya dukungan menyeluruh dari pihak sekolah, kolaborasi aktif antarpendidik, pelatihan guru, dan pengembangan perangkat ajar berbasis kearifan lokal agar implementasinya lebih efektif, relevan, dan berkelanjutan sesuai kebutuhan peserta didik di era globalisasi.